Elastoplastic constitutive model considering the filling and cementation effects for gas hydrate-bearing sediments: development and finite element implementation - Yuan, Qingmeng; Liang, Qianyong; Liang, Jinqiang; Wang, Zhigang; Yang, Lin; Wu, Xuemin; Guo, Binbin; Dong, Yifei (Frontiers in Earth Science, 2025)
Dynamic evolution of hydrate filling and cementation effects significantly affects the mechanical behavior of gas hydrate-bearing sediments (GHBS). To analyze the strength and deformation characteristics of GHBS under varying effective confining pressures and hydrate saturations, we use the unified hardening model for clays and sands (CSUH model) as a framework. A compressive hardening parameter is introduced to describe the isotropic compression behavior. Additionally, cementation strength is incorporated to adjust the yield function, while state parameters are used to modify the potential strength. An elastoplastic constitutive model is developed to capture the strength, stiffness, dilatancy, and softening of GHBS. Based on the user-defined subroutine interface provided by ABAQUS and the modified Euler integral algorithm with error control, the user-defined subroutine (UMAT) is embedded in ABAQUS to implement the finite element model. Numerical solutions are obtained, and the accuracy of the model is verified by comparing theoretical solutions with experimental data, showing good agreement. The results demonstrate that the model accurately represents the stress-strain relations and shear dilatancy characteristics of GHBS under various conditions. Furthermore, the model effectively evaluates the mechanical responses of GHBS with different hydrate formation behaviors under various environmental loads. These findings provide a foundation for further engineering applications.